The Safe Passage Study: Design, Methods, Recruitment, and Follow‐Up Approach. Issue 5 (5th August 2014) - Dukes, Kimberly A.; Burd, Larry; Elliott, Amy J.; Fifer, William P.; Folkerth, Rebecca D.; Hankins, Gary D.V.; Hereld, Dale; Hoffman, Howard J.; Myers, Michael M.; Odendaal, Hein J.; Signore, Caroline; Sullivan, Lisa M.; et al.
Abstract Background The Safe Passage Study is a large, prospective, multidisciplinary study designed to (1) investigate the association between prenatal alcohol exposure, sudden infant death syndrome (SIDS), and stillbirth, and (2) determine the biological basis of the spectrum of phenotypic outcomes from exposure, as modified by environmental and genetic factors that increase the risk of stillbirth, SIDS, and in surviving children, fetal alcohol spectrum disorders. Methods The results provided are based on an interim assessment of 6004 women enrolled, out of the 12 000 projected, from the Northern Plains, US, and Cape Town, South Africa, areas known to be of high risk for maternal drinking during pregnancy. Research objectives, study design, and descriptive statistics, including consent, recruitment, and retention information, are provided. Results Overall visit compliance is 87%, and includes prenatal, delivery/newborn, and postnatal contacts through 1 year post‐delivery. Pregnancy outcome ascertainment is 98% prior to medical chart review; less than 2% of women withdraw. Consent for the use of DNA and placental tissue exceed 94%, and consent to participate in the autopsy portion of the study is 71%. Conclusions The Safe Passage Study is the first multi‐site study of SIDS and stillbirth to integrate prospectively collected exposure information with multidisciplinary biological information in the same maternal and fetal/infant dyad using a common protocol. Essential components of the study design and its success are close ties to the community and rigorous systems and processes to ensure compliance with the study protocol and procedures.